Evidence on social and economic dimensions of informal caregiving in Slovenia - Ponikvar, Nina (Central European Public Administration Review, 2026)
Purpose: This paper examines key socio-demographic and health characteristics of informal caregivers and selected lifestyle pattern indicators in Slovenia. It also provides estimates of the economic value of unpaid caregiving.Design/methodology/approach: Using nationally representative data (n =1,075) collected in 2025 through a comprehensive questionnaire, we provide evidence on caregiver profiles through logistic regression modelling.Findings: The results indicate that older age and engagement in flexible or self-directed forms of employment significantly increase the likelihood of providing informal care, while notable differences emerge in the prevalence of specific health conditions, mental well-being indicators, and lifestyle patterns between caregivers and non-caregivers. Self-reported general health status does not differ significantly across the two groups, yet caregivers exhibit higher rates of musculoskeletal disorders, injuries, and certain chronic conditions. By combining data from the questionnaire with estimates from other large-scale studies on caregivers’ and their caregiving time, we estimate the economic value of unpaid caregiving at €2.1–€4.1 billion, representing approximately 3–6% of Slovenia’s GDP.Academic contribution to the field: This study contributes to the academic literature by providing the important nationally representative evidence on the socio-demographic, health, and lifestyle characteristics of informal caregivers in Slovenia. It advances research on the economics of care by combining caregiver profiling with macroeconomic valuation, thereby linking micro-level health and employment data with macro-level cost estimates of unpaid caregiving.Research implications: The findings underscore the substantial but largely unrecognised contribution of informal caregivers to the national long-term care system and emphasise the importance of considering the burden of informal care in designing not only social and health policies but also labour market measures addressing the well-being and workability of caregivers, thereby enabling sustainable complementarity between informal care and formal care systems. The evidence highlights the need to integrate support for informal caregivers into social, health, and labour market policies to sustain their ability to work and ensure the complementarity of informal and formal care. Future research could build on these findings by adopting longitudinal approaches to assess causal effects of caregiving on health and labour market outcomes.Originality/significance/value: This study combines nationally representative survey data on caregiver characteristics in Slovenia with macroeconomic valuation of unpaid caregiving, providing novel evidence for policy and research.
Keywords: dobro počutje; dolgotrajna oskrba; employment of invalids; long-term care; Slovenia; Slovenija; well-being; zaposlovanje invalidov